HIV and Depression: Examining Medical Students Clinical Skills - Rivera-Segarra, Eliut; Carminelli-Corretjer, Paola; Varas-Díaz, Nelson; Neilands, Torsten B.; Yang, Lawrence H.; Bernal, Guillermo (Frontiers in Psychiatry, 2020)
Major depression is a prevalent psychiatric disorder among people living with HIV (PWH). Major depression symptoms, including suicidal ideation, can hinder clinical care engagement and anti-retroviral treatment adherence. Research suggests that inquiry about major depression symptomatology and suicidal ideation should be standard practice when offering primary care services to PWH. However, studies examining depression and suicidal ideation inquiry are scarce. This study’s aim was to describe medical students’ clinical skills for dealing with major depression symptomatology and suicidal ideation among PWH in Puerto Rico. A total of 100 4th year medical students participated in a Standardized Patient simulation with a trained actor posing as a PWH and with a previous major depression diagnosis. One-way frequency tables were used to characterize the sample and the percentage of each observed clinical skill. Two key findings stem from these results: only 10% of the participants referred the patient to psychological/psychiatric treatment, and only 32% inquired about suicidal ideation. Our findings highlight the need for enhancing medical students’ competencies regarding mental health issues, particularly when providing services to at risk populations such as PWH within primary care settings.